INITIATIVES TO IMPROVE THE ABILITY OF TEACHERS TO PLAN AND IMPLEMENT ONLINE LEARNING THROUGH ACADEMIC SUPERVISION IN SDN KAPASARI VIII SURABAYA YEAR 2020/2021 - Rini Winarsih (LPPM STAI Muhammadiyah Probolinggo, 2021)
This research was conducted to describe Efforts to Improve Teachers' Ability in Planning and Implementing Online Learning Through Academic Supervision. Based on the results of initial observations, it was found that the teacher's performance was low, namely 15 teachers, both civil servants and non-civil servant teachers. The method that will be used in this research is School Action Research. This action research was carried out at SDN Kapasari VIII Surabaya, which began in March 2021. The results showed that through academic supervision, teachers could improve the ability of teachers to plan and implement the teaching and learning process at SDN Kapasari VIII Surabaya. The learning implementation plan assessment score increased by 27.9% from the first cycle with an average of 3.4 to an average of 4.4 in the second cycle, while the learning implementation assessment score increased 16.8% from the first cycle with an average of 3.7 to an average of 4.3 in the second cycle